Pathogenicity of Pratylenchus penetrans to dwarfing apple rootstocks - Bélair, Guy; Dauphinais, Nathalie; Fournier, Yvon (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2019)
The objective of this research was to measure the effect of P. penetrans densities on the vegetative growth of three apple dwarfing rootstocks Bud 9, M.9 and M.26 under field microplot conditions. Under 500 nematodes kg-1 soil density, the shoot dry weights of Bud 9, M.9 and M.26 rootstocks were significantly reduced by 30%, 23% and 14% respectively. Under the 1 500 nematodes kg-1 soil density, the dry shoot weight of Bud 9 and M.9 were not significantly different from the 500 nematodes kg-1 soil density except M.26 which exhibited a 29% decrease. The root dry weights of rootstocks were not significantly reduced when exposed to these P. penetrans densities except M.26 which was reduced 26% relative to non-inoculated trees under the 1 500 nematodes kg-1 soil density. These results confirm the pathogenic effect of P. penetrans on dwarfing apple rootstocks. Although preliminary, these results suggest some tolerance of M.26 to P. penetrans under lower density when compared to M.9 and Bud 9. Under higher nematode densities, both Bud 9 and M.9 exhibited a tolerance of their root system in comparison to M.26. Our results also emphasize the need to further assess the susceptibility/tolerance of dwarfing apple rootstocks to various densities of P. penetrans.